Effect of dietary zinc nanoparticle supplementation on mineral balance, tissue minerals status and immune response in Guinea pigs - UNIYAL, SANDEEP; GARG, ANIL KUMAR; CHAUDHARY, SANDEEP KUMAR (The Indian Journal of Animal Sciences, 2020)
The present study was designed to examine the effect of dietary supplementation of zinc nanoparticles on mineral balance, tissue minerals status and immune response in guinea pigs. Depending upon the source of Zn, 30 weaned male guinea pigs were randomly allocated to five different groups having 6 animals in each group in CRD. Animals under group T1 (control) were fed with basal diet with inorganic Zn (ZnSO4), whereas, animals were fed with organic Zn (Zn methionine) in group T2, commercial zinc nanoparticle in group T3 and two other zinc nanoparticles prepared in our laboratory in groups T4 and T5, respectively. They were supplemented with 20 mg Zn/kg feed on dry matter basis for 90 days. Results revealed that intake and balance of nitrogen and minerals (calcium, phosphorus, Zn and Cu) was not affected (P>0.05) by supplementation zinc nanoparticles. The level of Zn in liver and testes was significantly higher (P<0.05) in the zinc supplemented groups, when compared to that of control group, however, the mean values of Cu, Fe and Mn were comparable (P>0.05) among different groups, irrespective of the source of Zn. The mean antibody titre was significantly (P<0.05) higher in the commercial nanoparticle supplemented group as compared to other groups. As evidenced in our study spanning 90 days of trial, zinc nanoparticles can be safely supplemented up to 20 ppm level in the diet of guinea pigs.